Processing, structure and properties of Al-matrix composites - Begg, H; Henry Begg (2013)
Three classes of Al-matrix composite were manufactured to combine dissimilar metals and incorporate structural hierarchy, in an attempt to develop unusual combinations of mechanical properties. The first class combined a brittle, nano-quasicrystalline forming Al-3Fe-2Cr-2Ti phase with a ductile Al-4Cu phase into a layered structure using low pressure plasma spraying (LPPS). By using a substrate with multi-scale topological features, an ultra-thick (>2mm) deposit was successfully sprayed, which was subsequently consolidated by hot rolling to reduce residual porosity. The microstructure comprised a 'brick-wall' structure consisting of a convoluted arrangement of inter-leaved discreet droplet splats. Structure-property relationships were studied for four volume fractions of ductile additions and in-situ electron microscopy of beams subjected to 3-point bending suggested the ductile additions were providing additional toughening to the composite by a crack-bridging mechanism. The second class of composite investigated highly deformed microstructures of Al with 20vol% additions of either Sn or Ti. Nano-scale fibrous structures of the minority additions were achieved via an accumulative extrusion method, where extruded rod was abraded, degreased, bundled and re-extruded. This process was repeated to create refined microstructures while retaining a large material section. Fracture properties were studied in three point bending and crack growth monitored using Digital Image Correlation (DIC) to produce strain fields of the deforming beam surface. Modest changes were observed in mechanical properties with weak interfaces between poorly bonded extruded rods dominating fracture behaviour. Whiskers formed on polished surfaces of extruded Al-20vol%Sn and were monitored in real time by electron microscopy. Growth rates of up to 2.8nm/s were measured, which exceeds re- ported values in the literature on electroplated coatings by at least one order of magnitude. This may provide a convenient new means of studying whisker formation and calls into question current growth models. The third class of composite combined heavily rolled sheets of Al-20vol%Sn and Al-20vol%Ti with glass fibre/epoxy sheets to produce a laminate with multi-scale architecture. This laminate was designed as a proof-of-concept hierarchical material with structures ranging from the near millimetre scale of the metal-polymer layers, to the micro-sized glass fibre reinforcement of the epoxy and the nano-scale filamentary/lamellar microstructure of the highly deformed metal sheets. Fracture of such laminates was investigated in 3-point bending with continuous optical monitoring.